How the composition of sandstone matrices affects rates of soil formation - Evans, Daniel L.; Quinton, John Norman; Tye, A. M.; Rodés, Á.; Rushton, J. C.; Davies, J. A. C.; Mudd, S. M. (Elsevier, 2021)
Soils deliver multiple ecosystem services and their long-term sustainability is fundamentally controlled by the rates at which they form and erode. Our knowledge and understanding of soil formation is not commensurate with that of soil erosion, in part due to the difficulty of measuring the former. However, developments in cosmogenic radionuclide accumulation models have enabled soil scientists to more accurately constrain the rates at which soils form from bedrock. To date, all three major rock types – igneous, sedimentary and metamorphic lithologies – have been examined in such work. Soil formation rates have been measured and compared between these rock types, but the impact of rock characteristics on soil formation rates, such as rock matrices and mineralogy, have seldom been explored. In this UK-based study, we used cosmogenic radionuclide analysis to investigate whether the lithological variability of sandstone governs pedogenesis. Soil formation rates were measured on two arable hillslopes at Woburn and Hilton, which are underlain by different types of arenite sandstone. Rates were faster at Woburn, and we suggest that this is due to the fact that the Woburn sandstone formation is less cemented that that at Hilton. Similarly, rates at Woburn and Hilton were found to be faster than those measured at two other sandstone-based sites in the UK, and faster than those compiled in a global inventory of cosmogenic studies on sandstone-based soils. We suggest that the cementing agents present in matrix-abundant wackes studied previously may afford these sandstones greater structural integrity and resistance to weathering. This work points to the importance of factoring bedrock matrices into our understanding of soil formation rates, and the biogeochemical cycles these underpin
Keywords: Saprolite; Cosmogenic radionuclide analysis; Weathering; Soil production; Soil formation